Opinions of Secondary School Students on the Use of Mobile Augmented Reality Technology in Science Teaching - Gonca Keçeci; Pelin Yıldırım; Fikriye Kırbağ Zengin (Universitas Pendidikan Indonesia, 2021)
Mobile augmented reality (MAR) draws attention in terms of providing a flexible learning process and environment. It is thought that learning environments can be more effective using MAR technology. The research aimed to determine the secondary school students' views on the use of MAR technology in science teaching. The research was conducted with 143 students studying in the sixth grade at two different secondary schools in Turkey. In the research, convergent parallel patterns from mixed-method patterns were used. For eight weeks, the research was carried out to cover the systems unit in our body, situated in the 6th-grade science course curriculum. During the process, the Anatomy 4D application was used in the experimental group during the procedure, and the science course curriculum was used in the control group. In this paper, a part of the mixed research, the qualitative data collected from the experimental group's semi-structured interview form and diaries were analyzed. Descriptive analysis was used to analyze the data. As a result of the research, although the students do not have a clear idea about AR and MAR technologies at the beginning of the application, it is observed that their thoughts change over time, and MAR applications are effective on the success of the course.